Shaped-beam radiosurgery state of the art - Schulz, Raymond A.; De Salles, Antonio A. F. (Springer, 2011)
Novalis® Shaped Beam Radiosurgery has set new standards by delivering highly precise radiation treatments to tumors anywhere in the body through the use of a proprietary multileaf collimator. By shaping the radiation beam to the exact contours of the tumor or lesion, Novalis permits maximum dose delivery to the entire tumor while protecting healthy tissue; this makes it eminently suitable for the treatment of irregularly shaped tumors. Novalis features 360° gantry rotation, stereoscopic kV X-ray imaging, and 6D robotic patient positioning. Dose delivery is typically achieved through fixed conformal beams, dynamic conformal arcs, and IMRT, and most brain treatments do not require an invasive head frame. This book provides a complete guide to radiosurgery treatments with Novalis. After a thorough discussion of the clinical and technical basis for Shaped Beam Radiosurgery, current clinical applications are considered in detail, including brain, body, skull base, and spinal tumors as well as arteriovenous malformations. Careful consideration is also given to future developments and applications, including new technologies that promise to offer even more accurate treatments. This state-of-the-art book will appeal to a wide audience of physicians and their multidisciplinary clinical and technical collaborators.